How Context Modification can Favor the Release of Past Experience in Vespula germanica Wasps, Enabling the Detection of a Novel Food Site - D'adamo, Paola (2014)
Vespula germanica wasps typically make consecutive trips between an undepleted food source and their nest. Hence, relocating a rewarded location is a recurrent activity during a wasp’s lifetime. While foraging, wasps continue searching over a previously rewarded location even when food is no longer available. Moreover, when food is displaced to a location nearby, wasps still visit the previously rewarded location. We aimed to study how the modification of the local context would affect the discovery of the novel food site. By displacing food and changing the local context after wasps had learned a certain task, we evaluated whether wasps found a new food location more rapidly than if contextual conditions remained unaltered. We found that when previously associated cues were modified, wasps were more likely to ‘give up’ searching at the old location than if these cues remained unaltered. Furthermore, we observed that a higher number of rewarding trials at the initial location resulted in greater time taken to detect the new feeder location.